THE CONCENTRATION OF DISSOLVED PHOSPHATE IN WATER MASS AND SEDIMENT STUDY CASE IN SERANG AND MLONGGO RIVER - Lilik Maslukah; Sri Yulina Wulandari; Hasana Kushadi Ratnasari (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2017)
ABSTRACTSerang and Mlonggo Estuaries are located in the Jepara Regency, Central Java. Serang Estuary is located between Kedungmutih and Kedungmalang Village, while Mlonggo Estuary is located between Slagi and Jambu Village. Citizens around Serang and Mlonggo Estuaries dumped the waterwaste, which taken by rivers into the sea, such as household activity, agriculture, fish farming as well as the rest of the processing. The wastewater contains organic material and nutrients such as phosphate and organic carbon. The purpose of this research are find out the value and distribution of total organic carbon and bioavailable phosphate in sediments also orthophosphate in water. This research was conducted on June 18 – 19th 2016. Primary data in this research were total organic carbon (TOC) andbioavailable phosphate (BAP) from sediments also orthophosphate from water samples. Secondary data of this research were currents velocities, water qualities, bathymetry map. This research used quantitative method. While purposive method was used to determine the location of sampling. The results of the research showed the average value of TOC in sediments in Serang and Mlonggo Estuaries were 19.018% and 10.086%; BAP were 1.35 µmol/g and 0.33 µmol/g; orthophosphate in water were 0.012 ppm and 0.021 ppm. In both areas, the values of TOC and BAP in sediments also orthophosphate in waters the more the marine areas tended to decrease. Key words: Total Organic Carbon, Bioavailable phosphate, Orthophosphate, Serang Estuary, Mlonggo Estuary